Case Report: Anti-GABAA Receptor Encephalitis in a Dog - Huenerfauth, Enrice I.; Bien, Christian G.; Bien, Corinna; Volk, Holger A.; Meyerhoff, Nina (Frontiers in Veterinary Science, 2022)
Autoantibodies against neurotransmitter receptors detected in cerebrospinal fluid (CSF) and serum are increasingly recognized in people with human autoimmune encephalitis causing severe neurological deficits, such as seizures and behavioral abnormalities. This case report describes the first encephalitis associated with antibodies against the γ-aminobutyric acid-A receptor (GABAAR) in a dog. A young male intact Cavalier King Charles Spaniel was presented with recent onset of initial multiple generalized tonic-clonic seizures progressing into a status epilepticus. Interictally, he showed alternating stupor and hyperexcitability, ataxia, pleurothotonus and circling behavior to the left side. Magnetic resonance imaging (MRI) of the brain showed breed-specific anatomical abnormalities. Standard CSF analysis was unremarkable. Despite treatment with multiple antiseizure medications (ASMs) seizures and behavior abnormalities sustained. Immunotherapy with dexamethasone was started on the fifth day after disease manifestation. This led to rapid improvement of clinical signs. An extensive antibody search in CSF and serum demonstrated a neuropil staining pattern on a tissue-based assay compatible with GABAAR antibodies. The diagnosis was confirmed by binding of serum and CSF antibodies to GABAAR transfected Human Embryonic Kidney cells. The serum titer was 1:320, the CSF titer 1:2. At the control visit 4.5 weeks after start of immunotherapy, the dog was clinically normal. The GABAAR antibody titer in serum had strongly decreased. The antibodies were no longer detectable in CSF. Based on clinical presentation and testing for GABAAR binding antibodies, this describes the first veterinary patient with an anti-GABAAR encephalitis with a good outcome following ASM and corticosteroid treatment.